Poluição difusa proveniente das águas resultantes da aplicação de água residuária da suinocultura na cultura do Pinhão Manso, sob chuva simulada - Penzin, Cristiane Fracaro (2017)
Threats to availability water quality in Brazil and in the world include population growth, urbanization, industrialization, forms of land use, agricultural production, climate change and pollution sources. In many properties it is common to observe the release of animal waste to the soil without having knowledge of the need for nutrients needed for both the soil and the tilth. Thus, this study aims to evaluate the potential for pollution of surface water when the wastewater use of swine applied on Jatropha (Jatropha curcas L.) due to different levels of rainfall and fertigation to provide results to guide the optimization of the use of liquid waste by producers, minimizing costs and environmental impacts.The experiment was conducted at the Agricultural College in Palotina - PR. The 18 (eighteen) experimental plots were designed and built in an area of 900 m 2, with a collector trough coupled to the parcel to receive only the surface runoff generated by the simulated precipitation. The wastewater was analyzed chemically according to the methodology of APHA, AWWA and WEF (1998) and samples of the drainage were collected after the occurrence of precipitation. The experimental design was completely randomized with replicates, being six treatments with three replicates. The results were submitted to analysis of variance with Tukey test at the 5% level of significance. In order to verify data normality and homogeneity of variances, the software Minitab, version 16 was used. The applied doses of swine waste water were in the proportion of 80 and 160 m3 ha-1. The results showed that the precipitation intensity of 90 mm favored the higher surface runoff compared to the lower precipitation and that the presence of ARS exerted influence on the flow volume, demonstrating that doses from 80 m³ ha-1 favor surface runoff in function Of the sealing caused in the soil by the organic material present in ARS.